ABSORBANCE SPECTRUM CARBON NANODOTS (C-DOTS) DAUN TEMBAKAU - Adelina Ryan Candra Dewi; Mahardika Prasetya Aji; Sulhadi Sulhadi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Synthesis of C-Dots of dried tobacco leaves have been successfully carried out. C- Dots produced in liquid form, it is proved that the leaves of tobacco containing nicotine (toxic), can be transformed into new things more beneficial for the application. Extraction of tobacco leaves using 90% alcohol and water for 3.5 hours. A precursor solution prepared by adding urea degan variation of 1-6 grams into 20 ml extraction results. Dots C- synthesis is done by heating the precursor solution hydrothermally using a furnace for 30 minutes at 300 Â° C temperature conditions. The physical properties of color C-Dots menunjukkam brown tobacco leaf to the color yellow. C-Dots from tobacco leaves that have been produced have absorption spectra of light at a wavelength of 398-430 nm. The maximum absorbance spectrum dihasilkn time of adding urea 1g. Energy gap when the addition of urea 1g have indigo ~ 2.25 eV and the energy gap when the addition of 2g to 6g urea have the same value of ~ 2.7 eV. When the addition of 2 g to 6 g of urea does not affect the energy gap C-Dots.Keyword : C-dots, leaf tobacco, absorbance, energy g